(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Heart health has become a critical issue in our modern world. The elevated risk of heart disease is an important problem for every person. The Internet of Things is among the most innovative new technologies to appear in recent years. An example of such a development is the heart rate monitor. In this paper, we propose a remote heart rate monitoring system based on Internet of Things technology to facilitate communication between the doctor and the patient. This system is designed using electronic sensors (Pulse Sensor, Easy Pulse Sensor V1.1) that measure the heart rate and then send it to the NodeMcu board, which in turn sends the data to the Firebase database, where an Android application was created and designed using the Android Studio program, which uses the Java programming language to receive data from the database in real time. We tested the system and compared it with both sensors, revealing that the Easy Pulse V1.1 sensor outperforms the pulse sensor in terms of accuracy.